Propuesta de un plan de acción para la prevención y reducción de riesgos ergonómicos en el Gobierno Autónomo Descentralizado de Pedernales. - Dueñas Navarrete, María Isabel (2016)
This work investigative it aimed to propose an action plan ergonomic in the administrative area in the Government autonomous decentralized municipal of Pedernales, for the prevention and reduction of occupational risks, which began with an interview with the director of human talent that found the flaws of the irrigation work exposed workers, also applied an observation to all headquarters departments to view risks ergonomic existing from This institution, it was also known that there are eight headquarters, was used, the method of field in order to visit the place of study, the method of bibliographic, that will collect information from magazines, books, web pages among others. Diagnosis of ergonomic risks began with the implementation of tools for materials, equipment and safety standards that the institution, then developed the matrix of prevention of labour risks for Headquarters departments, and through a this proceeded to design the plan of action in order to identify and classify the risks found , also were the corresponding evaluations which were given the respective solutions, finally concludes the following ergonomic risks are a sets of activities that affect the health of workers, and that these can be prevented taking precautions in the workplace and through this the worker carry out their activities effectively and efficiently.